Formal verification of kLIBC with the WP frama-C plug-in - Carvalho, Nuno (2014)
This paper presents our results in the formal verification of kLIBC, a minimalistic C library, using the Frama-C/WP tool. We report how we were able to completely verify a significant number of functions from <string.h> and <stdio.h>. We discuss difficulties encountered and describe in detail a problem in the implementation of common <string.h> functions, for which we suggest alternative implementations. Our work shows that it is presently already viable to verify low-level C code, with heavy usage of pointers. Although the properties proved tend to be shallower as the code becomes of a lower-level nature, it is our view that this is an important direction towards real-world software verification, which cannot be attained by focusing on deep properties of cleaner code, written specifically to be verified.